Functional XPB/RAD25 redundancy in Arabidopsis genome: characterization of AtXPB2 and expression analysis - Morgante, Patrícia Gleydes [UNESP]; Berra, C. M.; Nakabashi, M.; Costa, RMA; Menck, CFM; Van Sluys, M. A. (Elsevier B.V., 2005)
The xeroderma pigmentosum complementation group B (XPB) protein is involved in both DNA repair and transcription in human cells. It is a component of the transcription factor IIH (TFIIH) and is responsible for DNA helicase activity during nucleotide (nt) excision repair (NER). Its high evolutionary conservation has allowed identification of homologous proteins in different organisms, including plants. In contrast to other organisms, Arabidopsis thaliana harbors a duplication of the XPB orthologue (AtXPB1 and AtXPB2), and the proteins encoded by the duplicated genes are very similar (95% amino acid identity). Complementation assays in yeast rad25 mutant strains suggest the involvement of AtXPB2 in DNA repair, as already shown for AtXPB1, indicating that these proteins may be functionally redundant in the removal of DNA lesions in A. thaliana. Although both genes are expressed in a constitutive manner during the plant life cycle, Northern blot analyses suggest that light modulates the expression level of both XPB copies, and transcript levels increase during early stages of development. Considering the high similarity between AtXPB1 and AtXPB2 and that both of predicted proteins may act in DNA repair, it is possible that this duplication may confer more flexibility and resistance to DNA damaging agents in thale cress. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Arabidopsis thaliana; gene duplication; nucleotide excision repair; ultraviolet irradiation